The Factors Restricting Economic Papuan Students Learning Difficulties Grantee LPMAK - Kurnia Sari, Rut Ervianna; Kardoyo, Kardoyo; Thomas, Partono (Journal of Economic Education, 2017)
Research objectives to find out and analyze the factors that hinder student's learning difficulties Papua grantee LPMAK on economic subjects. This research is descriptive research approach to mix method. The subject in this study is the whole student scholarship recipients Papua LPMAK totaled 52 students. Data collection is done with the now, interview and documentation. Data analysis was done with the analysis of factors and descriptive data analysis. Data collection is done with the now, interview and documentation. Data analysis was done with the analysis of factors and descriptive data analysis. The results showed there is a dominant factor that inhibits student learning difficulties Papua grantee LPMAK in Semarang City: Factors of mass media and the social environment, the use of mass media overload causing trouble Learning (learning difficulty) students. The head of Papua's Dormitory (teachers) will need to limit the activity of the child his protégé in the use of mass media and association with students of Papua and the media in the dorm.